(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The current stage of development of market relations in Uzbekistan requires serious decisions from local enterprises to increase the efficiency of their activities. Of particular interest to practical economists is the assessment of the efficiency of production activities, the cost of economic resources, as well as the introduction of accurate information technologies and ensuring the innovative functioning of enterprises. Most companies themselves prefer innovation in production. Despite all efforts to achieve the goal, in rare cases an enterprise can profit from successful innovations according to the standards of specialists.